A mendelian randomization study revealing that metabolic syndrome is causally related to renal failure - Cai, Xianfu; Wang, Decai; Wang, Jianjun; Ding, Chenguang; Li, Yang; Zheng, Jin; Xue, Wujun (Frontiers in Endocrinology, 2024)
The onset and progression of chronic kidney disease (CKD) has been linked to metabolic syndrome (MetS), with the results of recent observational studies supporting a potential link between renal failure and MetS. The causal nature of this relationship, however, remains uncertain. This study thus leveraged a Mendelian Randomization (MR) approach to probe the causal link of MetS with renal failure.Methods: A genetic database was initially used to identify SNPs associated with MetS and components thereof, after which causality was evaluated through the inverse variance weighted (IVW), MR-Egger regression, and weighted media techniques. Results were subsequently validated through sensitivity analyses.Results: IVW (OR = 1.48, 95% CI = 1.21-1.82, P =1.60E-04) and weighted median (OR = 1.58, 95% CI =1.15-2.17, P = 4.64E-03) analyses revealed that MetS was linked to an elevated risk of renal failure. When evaluating the specific components of MetS, waist circumference was found to be causally related to renal failure using the IVW (OR= 1.58, 95% CI = 1.39-1.81, P = 1.74e-11), MR-Egger (OR= 1.54, 95% CI = 1.03-2.29, P = 0.036), and weighted median (OR= 1.82, 95% CI = 1.48-2.24, P = 1.17e-8). The IVW method also revealed a causal association of hypertension with renal failure (OR= 1.95, 95% CI = 1.34-2.86, P = 5.42e-04), while renal failure was not causally related to fasting blood glucose, triglyceride levels, or HDL-C levels.: These data offer further support for the existence of a causal association of MetS with kidney failure. It is thus vital that MetS be effectively managed in patients with CKD in clinical settings, particularly for patients with hypertension or a high waist circumference who are obese. Adequate interventions in these patient populations have the potential to prevent or delay the development of renal failure.